2018
DOI: 10.3390/su10103532
|View full text |Cite
|
Sign up to set email alerts
|

Valuations and Decisions of Investing in Corporate Social Responsibility: A Real Options Viewpoint

Abstract: Corporate social responsibility (CSR) implementation could raise corporate reputations and benefit long-term development. Studying the effects of CRS on corporate valuation is essential. However, studies on the valuation of CSR are limited, particularly studies involving a dynamic model for valuing CSR. This study applies a real options approach to derive the company valuation of CSR investments, CSR options value, and the optimal timing for implementing CSR. This study elucidates the value of CSR and the deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
2
0
2
Order By: Relevance
“…Chen et al (2019) poukazují na to, že implementace konceptu CSR je nejistá investice pro společnosti, protože nevědí, co jim náklady a přínosy implementace filosofie CSR přinesou. Na druhé straně mnoho společností v současné době začíná alokovat prostředky na strategické aktivity CSR, protože si uvědomují, že jim to může pomoci zlepšit jejich ekonomické ukazatele v dlouhodobém horizontu (Lee, 2018). Hahn et al (2015) uvádí, že společnosti musí svou ekonomickou udržitelnost zaměřit stejně na ekonomické, environmentální a sociální aspekty, a že jeden aspekt nemůže mít přednost před ostatními, i když to často přináší problémy při rozhodování.…”
Section: Literární Rešeršeunclassified
See 1 more Smart Citation
“…Chen et al (2019) poukazují na to, že implementace konceptu CSR je nejistá investice pro společnosti, protože nevědí, co jim náklady a přínosy implementace filosofie CSR přinesou. Na druhé straně mnoho společností v současné době začíná alokovat prostředky na strategické aktivity CSR, protože si uvědomují, že jim to může pomoci zlepšit jejich ekonomické ukazatele v dlouhodobém horizontu (Lee, 2018). Hahn et al (2015) uvádí, že společnosti musí svou ekonomickou udržitelnost zaměřit stejně na ekonomické, environmentální a sociální aspekty, a že jeden aspekt nemůže mít přednost před ostatními, i když to často přináší problémy při rozhodování.…”
Section: Literární Rešeršeunclassified
“…Jak uvádí Menichini a Rosati (2014), výkon CSR závisí na těch dimenzích a zúčastněných stranách, které jsou skutečně ovlivněny aktivitami společnosti. Lee (2018) uvádí, že většina výzkumů CSR se zaměřuje především na vztahy se zákazníky a vztahy se zaměstnanci zůstávají do značné míry neprozkoumané. Podle autorů je vnímání aktivit CSR zaměstnanci velmi důležité pro vztahy na pracovišti, ale také pro výkon společnosti, protože zaměstnanci, kteří vnímají CSR příznivě, mají pozitivní vztah k organizaci v mnoha oblastech.…”
Section: Literární Rešeršeunclassified
“…We consider in this paper a simple model (see Appendix for a general model; see also Lee, ) that illustrates the stories of RWE and E.ON. The basic decision of the firm in our model is to decide whether an investment, which creates negative environmental externalities, should be undertaken right now or postponed.…”
Section: The Modelmentioning
confidence: 99%
“…The study found that the higher the incidence of multiple unexpected events, the greater the value of the investment opportunity and the longer the wait for the best investment opportunity. Lee (2018) adopted the real options approach to study corporate social responsibility (CSR), which is conducive to the long-term development of a company and can improve corporate reputation. The study clarifies the value of CSR and the decision to invest in CSR.…”
Section: Introductionmentioning
confidence: 99%